2020
DOI: 10.1021/acsnano.0c04813
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Optical Transitions in Metal Nanoclusters

Abstract: Currently, a comprehensive understanding of the relationship between atomic structures and optical properties of ultrasmall metal nanoclusters with diameters between 1 and 3 nm is lacking. To address this challenge, it is necessary to develop tools for perturbing the atomic structure and modulating the optical properties of metal nanoclusters beyond what can be achieved using synthetic chemistry. Here, we present a systematic high-pressure study on a series of atomically precise ligand-protected metal nanoclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…This is proposed as one of the possible reasons for the emergence of the peak at 575 nm. Under high pressures, red shifts of the absorption and the emission onset of the Au 21 (SR) 12 (dppm) 2 (SR = cyclohexanethiolate; dppm = bisdiphenylphosphinemethane) and Au 28 (S-TBBT) 20 (S-TBBT = tert -butyl-benzenethiolate) NCs were shown in a recent report . This red shift is due to the narrowing of the energy levels of NCs because of the delocalization of the core electrons to the ligands under compression.…”
Section: Results and Discussionmentioning
confidence: 89%
“…This is proposed as one of the possible reasons for the emergence of the peak at 575 nm. Under high pressures, red shifts of the absorption and the emission onset of the Au 21 (SR) 12 (dppm) 2 (SR = cyclohexanethiolate; dppm = bisdiphenylphosphinemethane) and Au 28 (S-TBBT) 20 (S-TBBT = tert -butyl-benzenethiolate) NCs were shown in a recent report . This red shift is due to the narrowing of the energy levels of NCs because of the delocalization of the core electrons to the ligands under compression.…”
Section: Results and Discussionmentioning
confidence: 89%
“…This explains why their measured PL lifetimes are generally from hundreds of nanoseconds to several microseconds. Meanwhile, the low absorption coefficient could make the band-edge transition “invisible” in the absorption spectrum; thus, the observed the large Stokes shifts in many nanoclusters are actually the energy difference between higher energy absorption transition and the PL. , Second, many gold nanoclusters show rich structure–relaxation/transformation processes under excitation, and these significant excited-state processes could increase the Stokes shifts.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, the Aikens group conducted a series of computational studies on the mechanism of the PL enhancement in gold nanoclusters. ,, In our previous studies, significant enhancement of the PL QY was achieved by tailoring the surface structures, , embedding nanoclusters into polymers, and dissolving the nanocluster in viscous solvents . Most notably, our recent results show that the PL of gold nanoclusters can be significantly enhanced by increasing pressure …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 But so far only a couple of experimental studies have explored their high-pressure properties. Gu et al 36 reported the first highpressure optical study of a series of fcc and bitetrahedral nanoclusters, including Au21(SR)12, Au28(SR)20, Ag28Pt(SR)18, Au24(SR)20, and Au14Cd(SR)12. They observed a red shift in the absorption onset with increasing pressure up to ∼12 GPa in all the studied ulatrasmall nanoclusters and an up to 200-fold enhancement in the photoluminescence at pressures around 7 GPa.…”
Section: Introductionmentioning
confidence: 99%